Complexities in a Plant-Herbivore Model - Rajni SHARMA; L.M.SAHA (Journal of Applied Computer Science & Mathematics, 2017)
A simple host-parasite type model has been considered to study the interaction of certain plants and herbivores. The two dimensional discrete time model utilizes leaf and herbivore biomass as state variables. The parameter space consists of the growth rate of the host population and a parameter describing the damage inﬂicted by herbivores. Perceptive bifurcation diagrams, which give insightful results, have been present here showing chaos and complexity in the system during evolution. Measure of complexity and chaos in the system be explained by performing numerical calculations and obtaining Lyapunov exponents, topological entropies and correlation dimension. Results are displayed through interesting graphics.